2021
DOI: 10.1126/sciadv.abi4717
|View full text |Cite
|
Sign up to set email alerts
|

Public good exploitation in natural bacterioplankton communities

Abstract: Bacteria often interact with their environment through extracellular molecules that increase access to limiting resources. These secretions can act as public goods, creating incentives for exploiters to invade and “steal” public goods away from producers. This phenomenon has been studied extensively in vitro, but little is known about the occurrence and impact of public good exploiters in the environment. Here, we develop a genomic approach to systematically identify bacteria that can exploit public goods prod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Our CR model and fitting procedure can also be used to aid the parametrization of other models such as Lotka-Volterra models ( Figure 4—figure supplements 1 – 5 ), comparisons among which can reveal the model details that are required to recapitulate experimental data. In the future, more detailed hypotheses can be generated by investigating how time series statistics are affected by modifications to baseline CR dynamics, such as the incorporation of metabolic cross-feeding ( Goldford et al, 2018 ; Li et al, 2020 ) or physical interactions such as type VI killing ( Verster et al, 2017 ), functional differentiation from genomic analysis ( Arkin et al, 2018 ; Machado et al, 2021 ; Pollak et al, 2021 ), and physical variables such as pH ( Aranda-Díaz et al, 2020 ; Ratzke and Gore, 2018 ), temperature ( Lax et al, 2020 ), and osmolality ( Cesar et al, 2020 ). In addition, recent studies have shown that evolution can substantially affect the dynamics of human gut microbiotas ( Garud et al, 2019 ; Yaffe and Relman, 2020 ; Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our CR model and fitting procedure can also be used to aid the parametrization of other models such as Lotka-Volterra models ( Figure 4—figure supplements 1 – 5 ), comparisons among which can reveal the model details that are required to recapitulate experimental data. In the future, more detailed hypotheses can be generated by investigating how time series statistics are affected by modifications to baseline CR dynamics, such as the incorporation of metabolic cross-feeding ( Goldford et al, 2018 ; Li et al, 2020 ) or physical interactions such as type VI killing ( Verster et al, 2017 ), functional differentiation from genomic analysis ( Arkin et al, 2018 ; Machado et al, 2021 ; Pollak et al, 2021 ), and physical variables such as pH ( Aranda-Díaz et al, 2020 ; Ratzke and Gore, 2018 ), temperature ( Lax et al, 2020 ), and osmolality ( Cesar et al, 2020 ). In addition, recent studies have shown that evolution can substantially affect the dynamics of human gut microbiotas ( Garud et al, 2019 ; Yaffe and Relman, 2020 ; Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…After discarding the supernatant, the cells were washed with 1 ml of MBL minimal medium medium without carbon source. Cells were centrifuged again and the cell pellet was resuspended in 1 ml of MBL (marine minimal medium) [ 30 , 34 ] adjusted to an 0.002 OD600. Cells from these cultures were used for experiments in MBL minimal medium containing 0.1% (weight/volume) Pentaacetyl-Chitopentaose (Megazyme, Ireland).…”
Section: Methodsmentioning
confidence: 99%
“…On the surface, these studies support the reductionist notion that degradation rates can be understood by focusing solely on hydrolase repertoires. However, degradation rates could be affected by many other traits, such as the ability to swim toward breakdown products and uptake them into the cell, among others (Pollak et al, 2021). To what extent the ecological success of a degrader and the size of its hydrolase repertoire are directly or indirectly linked, remains unclear, but this is a tractable a problem that can be addressed with genetic model systems such as vibrios (Visick et al, 2018) or Z. galactanivorans (Zhu et al, 2017).…”
Section: Challenge 2 | Adaptive Vs Non-adaptive Evolution Of Enzyme Repertoiresmentioning
confidence: 99%
“…One process that can create this dynamicity is social cheating. Social interactions have been shown to be a relevant process in polysaccharide degrading marine and gut microbes, leading to loss-of-function mutants that exploit the hydrolysis byproducts released by degraders (Pollak et al, 2021). This form of social interaction can turn a highly fit degrader, with an optimal breakdown pathway, unfit in an environment with high population density (Gore et al, 2009).…”
Section: Challenge 2 | Adaptive Vs Non-adaptive Evolution Of Enzyme Repertoiresmentioning
confidence: 99%
See 1 more Smart Citation